Sources of resistance to Alternariaster leaf blight in sunflower pre-breeding lines derived from interspecific crosses and wild Helianthus species. (February 2017) - Santha Lakshmi Prasad, M.; Sujatha, M.; Alivelu, K.; Sujatha, K.
Abstract: Leaf blight caused by Alternariaster helianthi (Hansf.) Tubaki and Nishihara is one of the important diseases of sunflower that causes considerable yield loss. Resistance against leaf blight in the germplasm, parental lines and released sunflower cultivars is rather limited. Hence, screening of sunflower accessions comprised interspecific derivatives, core germplasm, pre-breeding lines, exotic lines and wild Helianthus species was carried out under natural field conditions over five years viz ., 2003 to 2009. Sunflower lines which showed resistance under field conditions were further confirmed under controlled conditions by artificial inoculation with A . helianthi . Among interspecific crosses evaluated, pre-breeding lines derived from crosses of cultivated sunflower with wild H . annuus (ANN-SF) followed by trispecific crosses of cultivated sunflower with H . argophyllus, wild H . annuus (ARG-ANN-SF) and cultivated sunflower with H . argophyllus (ARG-SF) showed less leaf blight disease under field conditions. The disease severity was greater during 2004–05, 2006–07, 2007–08 and 2009–10 which was favoured by high rainfall, many rainy days and high relative humidity. Six sunflower accessions showed less leaf blight severity. Of three A . helianthi isolates tested, Ah -112 was found to be highly aggressive causing more than 30% leaf blight severity on all tested cultivars. Among different wild Helianthus species tested against leaf blight by detached leaf and whole plant assay techniques, H . tuberosus Acc 03, 1705, 08, 07, 15, 2729, H . maximiliani Acc 007 and H . strumosus Acc 15 recorded <20% leaf blight severity in the whole plant assay method indicating some resistance. Appropriate strategies are being devised to utilize the interspecific accessions and wild Helianthus species identified to be moderately resistant to Alternariaster leaf blight in the sunflower breeding programmes. Highlights: Interspecific crosses involving cultivated sunflower with wild H . annuus, H . argophyllus showed less leaf blight. Disease severity was favoured by high rainfall, many rainy days and high relative humidity. Six sunflower pre-breeding accessions showed leaf blight severity scale of 3 in whole plant assay method. Wild Helianthus species, H . tuberosus, H . maximiliani and H . strumosus recorded <20% leaf blight severity.